A4.6 Nicotinic acetylcholine receptor ligands inhibit osteoclastogenesis by blocking RANKL-induced calcium-oscillation and induction of NFATC1 and CFOS. (31st January 2014) - Mandl, P; Győri, D; Karonitsch, T; Blüml, S; Hayer, S; Mócsai, A; Smolen, JS; Redlich, K
Abstract : Background/Objectives: We have previously shown that nicotinic acetylcholine receptors (nAChRs) are key regulators of osteoclastogenesis (1). NAChRs permit the movement of Ca2+, the intracellular oscillation of which is known to play an essential role in mediating the effects of RANKL on osteoclastogenesis. We therefore elucidated the potential effects of nAChR ligands on RANKL-induced Ca2+ oscillation. To assess downstream elements of the RANK pathway, we also evaluated their effect on the transcription factors NFATc1 and c-fos. Methods: For intracellular Ca2+ -measurement, murine osteoclast precursors (pOCs) were incubated with 5 μM Fura-2-AM and 0.05% pluronic F-127 for 30min at 37°C, then post-incubated in HBSS media containing Ca2+. Intracellular Ca2+ levels were detected with a fluorescent microscope (Visitron Systems). Images were scanned and plotted at 5sec intervals at 340 and 380 nm wavelengths. Evaluation of images was carried out with MetaFluor software. Quantitative RT-PCR was performed using mRNA extracted from osteoclasts and the amount of dsDNA was quantified using SYBR Green I as detected by a LightCycler (Roche Molecular Biochemicals). For Western blot, BMMs were incubated with M-CSF for 1-7 days and treated with RANKL and/or nicotine. Protein extracts were separated by electrophoresis on acrylamide gel, followed by electrotransfer onto nitrocellulose membrane and incubation with monoclonal antibodies against NFATc1, c-fos and actin. Results: POCs show characteristic Ca2+ oscillations after 72h treatment with RANKL. Treatment with the nonspecific nAChR agonist nicotine, its physiological ligand acetylcholine (ACh) and the α7 nAChR agonist PNU-282987 led to marked, immediate abrogation of RANKL-induced Ca2+ oscillation. To evaluate the nature of this inhibition, we added the α7 nAChR antagonist alpha-BTX, which caused a similar effect. We next added the non-specific nAChR antagonist mecamylamine shortly before treating oscillating BMMs with ACh, and found that in such conditions ACh failed to inhibit Ca2+ oscillations. In pOCs subjected to prolonged exposure (72h) with high-dose nicotine, concomitant treatment with RANKL failed to induce characteristic Ca2+ oscillations. In qPCR and Western blot experiments nicotine inhibited the induction of c-fos and NFATc1 after 24h stimulation with RANKL and reduced the production of NFATc1 isoforms B and C after 7 days of stimulation with RANKL. Conclusions: We have shown that nAChR ligands inhibit Ca2+ -oscillation in pOCs, which blocks the RANKL-induced expression and accumulation of c-fos and NFATc1. These results elucidate our earlier findings that nAChRs are key players in the regulation of osteoclastogenesis in mice. References: Mandl P et al . Ann Rheum Dis 2011;70:99